The effect of electrical stimulation on recovery from exercise-induced muscle damage. Issue 15 (10th November 2011) - Leeder, J; Spence, J; Taylor, E; Harrison, A; Howatson, G
Abstract : The aim was to investigate the efficacy of a commercially available electrical stimulation device purporting to facilitate recovery from strenuous exercise. Eight participants (5 male and 3 female, age range 23–30 y) volunteered for the study and were familiarised with all exercises involved. Prior to damaging exercise, participants completed tests of maximal isometric voluntary contraction of the knee extensors (MIVC-E) and flexors (MIVC-F) of both legs and perception of delayed-onset muscle soreness (DOMS) was ascertained via a 200 mm visual analogue scale. To induce muscle damage, participants completed 5 sets of 20 drop jumps (10 s between jumps, 2 min between sets) from a 60 cm (males) or 40 cm high (females) platform. Electrical stimulation (Bodyflow, Victoria, Australia) was applied at 1.52 Hz for 3×20 min per day, separated by 5 h, for the next 48 h, randomised into either the dominant ( n = 4) or non-dominant leg ( n = 4), with the contralateral leg acting as the non-treatment control. Participants completed tests of MIVC-E and MIVC-F and a visual analogue scale 24 h and 48 h following the exercise insult. DOMS showed an increase over time ( p <0.05), peaking at 48 h (119±45 mm). MIVC-E showed a reduction over time ( p <0.05), indicating muscle damage was present, but MIVC-F showed no reduction over time ( p >0.05). There were no effects of treatment, or interactions between treatment and time for muscle function or muscle soreness ( p >0.05). At 24 h after exercise, relative reductions in MIVC-E for control and treatment groups were 16±8% and 11±7%, respectively, and at 48 h 8±8% and 5±8%, respectively. Electrical stimulation was not effective at alleviating perceptions of DOMS following muscle damaging exercise, but there was a trend towards accelerated recovery of knee extensor strength. Further research is required to elucidate this finding with a larger and more homogenous sample population.